Fostering National Pride and Aesthetic Taste in Students through Batik Artworks - Kenjayeva Umida Rajabovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ABSTRACT: This article explores the role of batik artworks in fostering national pride and aesthetic taste among students. Batik, a traditional wax-resist dyeing technique, carries rich cultural and historical significance, reflecting the artistic heritage of various communities. The study emphasizes how engaging with batik helps students develop an appreciation for national traditions while enhancing their visual and aesthetic sensibilities. By analyzing patterns, motifs, and color schemes, students gain insight into cultural symbolism, artistic expression, and design principles. The article also highlights pedagogical strategies for integrating batik into classroom and extracurricular activities to cultivate both cultural identity and aesthetic awareness. Overall, batik serves as an effective educational tool for nurturing students’ creativity, cultural understanding, and appreciation for beauty.